Assessment of Hearing Following Tympanoplasty - A Hospital Based Study - Jyoti, Deep; Saraf, Aditiya; ., Arti (International Journal of Innovative Research in Medical Science, 2019)
Aims & Objectives: to assess the hearing outcome in patients of chronic otitis media undergoing tympanoplasty. Material & Methods: A total of 100 patients between age group of 18 to 50 years attending the ENT OPD of SMGS Hospital, GMC Jammu between February 2018 and January 2019, were included in our study. Inclusion criteria for our study were patients of both safe and unsafe ears with good cochlear reserve and adequate eustachian tube function. Exclusion criteria for our study were patients with sensorineural hearing loss or mixed hearing loss, malignancy, otitis externa and any complication of chronic otitis media. Results: Mean pre-operative and post-operative hearing loss in all patients according to the tympanoplasty done showed that there is a gain of 14.34 dB in Type I, 19.59 dB in Type II and 18.29 dB in Type III. Conclusion: Tympanoplasty is an effective operation for hearing improvement and eradication of disease from middle ear.